f(f(

g(g(

TRS

↳Removing Redundant Rules

Removing the following rules from

g(g(x)) -> f(x)

where the Polynomial interpretation:

was used.

_{ }^{ }POL(g(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1})= 1 + x _{1}_{ }^{ }

Not all Rules of

TRS

↳RRRPolo

→TRS2

↳Removing Redundant Rules

Removing the following rules from

f(f(x)) -> g(f(x))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(g(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1})= 1 + x _{1}_{ }^{ }

All Rules of

TRS

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳Dependency Pair Analysis

Duration:

0:00 minutes